Prevalence of Overweight, Obesity and Underweight among School Going Children in Rural and Urban areas of Thiruvananthapuram Educational District, Kerala State (India) - Ambily G. Unnithan S. Syamakumari (The Internet Journal of Nutrition and Wellness. 2008 Volume 6 Number 2, 2008)
Objective: Objective of this study was to assess the prevalence of overweight, obesity and under weight among school children in the rural and urban areas of Thiruvananthapuram Educational District. Methodology: A total of 3886 children from 10-15 years of age were screened from rural and urban schools. Overweight and Obese children were then identified using the IOTF cut-off values3 Results: The results of the study exposed the fact that the percentage of overweight and obese children are growing in both rural and urban areas of Kerala like in other states of India and different of the world. The study also showed that when obesity and overweight were seen more in boys, underweight and severe underweight seemed to be more in girls indicating an increasing trend in the percentage of overweight in boys compared to girls. When the prevalence of overweight and obesity were higher among urban children, the percentage of underweight and severe underweight was higher among rural children. Conclusion: The increasing trend of the modern day epidemic of overweight / obesity in children calls for immediate action in both rural and urban areas to reduce the incidence through appropriate nutritional intervention programmes involving school children, their parents and school authorities